(untitled) (Foro de Educacion, 2023)
This essay presents some effects, in terms of social responsibility, of an education promoted and carried out under the principles of the market economy. It is stated that this economy, firstly, promotes a concept of freedom and autonomy dependent on purchasing power and level of education, secondly, it inhibits in students the sense of social responsibility and civic duty. In turn, this economic dynamics and the approach given to the educational system that strives to meet the needs of the market, can be explained by the concept of human being that some philosophical lines have developed, which ended up reducing it to a few affects and cognitive processes. The results of all this are the moral and cognitive weakening of the students and a low capacity to cope with social problems. Given this, it is proposed, once again, the strengthening of Aristotle’s moral and intellectual virtues, especially the virtue of prudence and good deliberation (eubolia), of which it is argued that they can allow a greater rapprochement of the human beings around common problems, and makes them less dependent on the will of state governments and economic systems.